(untitled) (Nonlinear Studies, 2013)
This paper studies the existence and uniqueness of solutions for a nonlocal boundary value problem of impulsive nonlinear integro-differential equations of fractional order. Some standard fixed point theorems are applied to obtain some new existence results. An illustrative example is also presented.